Efficient capture of fine particulate matters by ultrasonic atomization. Issue 5 (October 2021) - Cui, Ke; Pang, Xiaolong; Zhou, Zhiyong; Ren, Zhongqi
Abstract: In order to achieve efficient capture of fine particulate matters (the aerodynamic equivalent diameter between 0.01 and 5 µm), fiber filter dust removal equipment was employed. Ultrasonic atomization technology was used to improve the existing filtration and dust removal performance. Numerical simulations on the factors that influence the dust removal efficiency were conducted. By combining simulation results with experimental results, a novel ultrasonic atomized dust removal system was developed. The droplet resisting the airstream in the front of the filter could significantly improve the dust removal efficiency by increasing the thickness of filter from 8 cm to 16 cm and filling rate from 6.49% to 18.91% at low dust concentration as 0.7 g/m 3 . The highest dust removal efficiency was up to nearly 100%. However, adjusting the thickness of filter and filling rate had little effect on the dust removal efficiency at high dust concentration as 7.0 g/m 3 . The optimal operation conditions with thickness of filter as 8 cm, adding mode a, filling rate as 9.36%, wind speed as 5.0 m/s and mass ratio of droplet to dust as 3.5 and 1.2 for dust concentration of 0.7 and 7.0 g/m 3 were obtained. Sodium dodecyl sulfonate (SDS) was added as a surfactant to effectively enhance the agglomeration effect of fine particulate matters. In summary, the ultrasonic atomization technology performed well in terms of capturing fine particle matters and dust suppression. Graphical Abstract: ga1 Highlights: Fiber filter dust removal equipment was used to collect fine particulate matters. Ultrasonic atomization technology was employed to improve dust removal efficiency. Droplet resisting airstream in the front of filter showed best removal efficiency. Addition of SDS could enhance agglomeration effect, increasing dedusting efficiency.